Nowe wyzwania dla menedżerów na podstawie opinii pracowników wybranych organizacji gospodarczych - Stosik, Aneta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article includes the results of a study on management challenges in the context of preferred features and efficient leaders behaviours, from the perspective of tourism industries employee. The author also emphasizes the role of leader behaviours. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 109-115